Atomic Mechanism of Predictable Phase Transition in Dual‐Phase H2Ti3O7/TiO2 (B) Nanofiber: An In Situ Heating TEM Investigation. Issue 36 (23rd July 2014) - Lei, Yimin; Sun, Jie; Liu, Hongwei; Cheng, Xuan; Chen, Fuyi; Liu, Zongwen
Abstract The phase transition from H2Ti3O7 to TiO2 (B) in a 1D single nanocrystal of H2Ti3O7 was observed by in situ heating in a transmission electron microscope experimentally. The results indicate a typical monoclinic‐to‐monoclinic crystallographic orientation relationship between the two phases. Moreover, the fundamental building blocks and invariant deformation element model were both adopted to reveal the atomic mechanism and predict the crystallographic orientation relationship quantitatively for the phase transition. The prediction was precisely consistent with TEM results.